Balanced Scorecard como ferramenta de avaliação da consistência estratégica: um estudo em instituição de ensino superior privada - Lima Júnior, Gilberto Franco de (2008)
This Master of Science Thesis investigates in an exploratory modeling the idea of strategy consistency applying as an assessment tool a model of performance indicators of a higher education institution based on the balanced scorecard (BSC). It is carried on a review of conceptual BSC perspective hierarchy models and of studies on higher education institution in Brazil and worldwide. From a BSC model with three indicators at each perspective is carried on a case study with directors and coordinators of a private higher education institution with a descriptive and multivariate analysis using cluster analysis. The main findings point to a different perception of respondents on the importance level of the perspectives with a higher importance level given to Learning and Growth and Process that to Customer and Financial. Particularly, the financial perspective got a importance level significantly lower that the others, what suggests an inconsistency on the strategy deployment on the institution considered in terms of the perception of the managerial levels of the importance level of the perspectives